2022
DOI: 10.3390/life12030357
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Complications after COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is a threat to patients not only because of its acute course, but also because of various complications occurring in the following period, that is, more than 28 days after the onset of acute infection. The present study identified a total of 121 patients hospitalized 29 or more days after the first positive result of a PCR test for SARS-CoV-2, of whom 98 patients were included in the study. Patients were divided into two groups by the time interval between the positive COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Superinfections in critically ill COVID-19 patients are common due to various factors, such as the fact that SARS-CoV-2 may enhance colonization and attachment of bacteria to host tissue, not only during the illness itself, but also in the post-COVID phase [ 11 ]. Airway dysfunction, cytopathology and tissue destruction induced by SARS-CoV-2 infection or during bacterial co-infection may facilitate systemic dissemination of the virus and/or bacterial co-pathogens, dramatically increasing the risk of blood infections and sepsis [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Superinfections in critically ill COVID-19 patients are common due to various factors, such as the fact that SARS-CoV-2 may enhance colonization and attachment of bacteria to host tissue, not only during the illness itself, but also in the post-COVID phase [ 11 ]. Airway dysfunction, cytopathology and tissue destruction induced by SARS-CoV-2 infection or during bacterial co-infection may facilitate systemic dissemination of the virus and/or bacterial co-pathogens, dramatically increasing the risk of blood infections and sepsis [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This can be important in helping to understand the effectiveness of disease prevention and control strategies, as well as in ensuring the correct attribution of causes of death [ 44 ]. COVID-19 patients may develop chronic pulmonary complications [ 45 ] or other diseases as a result of the infection [ 46 , 47 , 48 , 49 ]. Forensic pathology can contribute to the understanding of these complications and the development of appropriate therapies, and provide guidelines on how to manage deaths safely and effectively to protect both staff and the public [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…If the immune response is excessive, long-term immune dysregulation may occur, increasing vulnerability to secondary infection and organ dysfunction, even after recovery from COVID-19 [ 10 , 14 , 15 ]. Immunocompromised patients are more susceptible to fungal diseases [ 13 ] and PCP is a lethal disease [ 28 ]. Recently, several studies have reported PCP superinfection in patients with severe COVID-19; however, there is no clear definition for distinguishing between infection and colonization [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following COVID-19 infections, 5–30% of patients experience long COVID, characterized by various complications [ 10 , 11 ]. The duration of long COVID is reported to be 9 months for hospitalized patients and 4 months for non-hospitalized patients, and the rate of hospitalization for respiratory symptoms following acute COVID-19 infections has increased [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%